Physical fitness and throwing speed in U13 versus U15 male handball players - Fernandez-Fernandez, J.; Granacher, U.; Martinez-Martin, I.; Garcia-Tormo, V.; Herrero-Molleda, A.; Barbado, D.; Garcia-Lopez, J. (BMC Sports Science, Medicine and Rehabilitation, 2022)
Background The aim of this study was to analyze the shoulder functional profile (rotation range of motion [ROM] and strength), upper and lower body performance, and throwing speed of U13 versus U15 male handball players, and to establish the relationship between these measures of physical fitness and throwing speed.